Legal innovation in Papua New Guinea, 1970-2015 - Demian, Melissa (UK Data Service, 2021)
Data collection of field notes relating to resolving conflicts in village and peri-urban Papua New Guinea contexts of the Village Court system. These are extremely sensitive in nature, as they contain much confidential and personal background relating to the participants in Village Court cases. We plan to make a version of this available in a database under active development, which will be heavily redacted and anonymised, but which we still think will be of value once complete, probably some time in 2017 or early 2018. Segments of the notes are in one of the pidgin varieties, most are in English. The field notes are held by the original researchers, who are willing to discuss access with appropriate researchers. Eventually these will be deposited with embargoes of twenty years with the Human Relations Area Files at Yale University (HRAF). Fischer is currently engaged in a project based on the notes with HRAF to auto-create very detailed metadata from sensitive documents such as field notes that preserve anonymity and confidentiality while relating much more detail of what is being described in the notes, based initially on HRAF's Outline of Cultural Materials ontology as applied by the Analysts at HRAF to ethnographic material. This project entails the collection and analysis of ethnographic data on the contemporary practices of Village Courts in Papua New Guinea. These courts, established at the country's independence in 1975, have had little or no state oversight in their 37-year history, resulting in a profound degree of variation in the way the courts currently operate. The research will in particular focus on irregularities in Village Court practice, including the hearing of cases outside of their jurisdiction, the hearing of cases by authorities other than appointed Village Court magistrates, and the participation of so-called 'bush lawyers', self-educated but otherwise unqualified advocates. The project is a collaboration between scholars in the anthropology of law in the United Kingdom and Australia, and will also include the participation of Papua New Guinean researchers. All researchers will document the practices of Village Courts in different regions of this highly diverse country, with the aim of counteracting a political rhetoric that the Village Courts are failing with actual evidence of the ways in which ordinary Papua New Guinean people have maintained and developed a system of justice and dispute management that works for them in the absence of state involvement or support. This project, in addition to its immediate follow on impact of Melissa Demian and Fiona Hukula through a World Bank Consultancy on VIolence and Women in PNG, has had an impact leading to further proposed research on agency, rights and justice aiming to inform policy relating the African Green Revolution in Mozambique, and informed proposed research on conforming robot behaviour to the expectations of human work groups.